Environmental Epigenetics: Effects of Endocrine Disruptors on Development of Obesity – Statistical Analysis - Kuno, Mika (Bioinformatics and Biomedical Research Journal, 2018)
Specific epigenetic alternation occurs by direct exposure to toxicants or abnormal nutrition, which influence disease development or physiological phenotypes. Previous study has demonstrated that exposure to endocrine disrupting compounds (EDCs) may contribute to excess adiposity and other features of dysmetabolism, accordingly, EDCs exposure may contribute to development of obesity, and insulin resistance, common precursors of type 2 diabetes and cardiovascular diseases. However, at this time, there is limited human data about contribution of environmental chemicals to the obesity epidemic. As obesity is a major public health problem in Indonesia, it is important to identify common environmental risk factors that may have a role in the development of obesity. Therefore, the objective of this study is to proof whether environmental factors/EDCs affect the development of obesity by using top-down approaches. Use two datasets, expression profile and methylation profile, from NCBI GEO database and apply statistical analysis to investigate the differentially expressed gene, analysis was conducted in R software and GEO2R web tool. Environmental epigenetics help to better understand how endocrine disruptors influences human health and disease, and there are two genes are found to be contribute to the weight gain. Further research is needed to have more confidence result of the analysis. Keywords: Epigenetics, obesitas, endocrine disruptor, environmental factor, statatistical analysis